The economic case for low-carbon development in rapidly growing developing world cities: A case study of Palembang, Indonesia. (May 2015) - Colenbrander, Sarah; Gouldson, Andy; Sudmant, Andrew Heshedahl; Papargyropoulou, Effie
Abstract: Where costs or risks are higher, evidence is lacking or supporting institutions are less developed, policymakers can struggle to make the case for low-carbon investment. This is especially the case in developing world cities where decision-makers struggle to keep up with the pace and scale of change. Focusing on Palembang in Indonesia, this paper considers the economic case for proactive investment in low-carbon development. We find that a rapidly growing industrial city in a developing country can reduce emissions by 24.1% in 2025, relative to business as usual levels, with investments of USD405.6 million that would reduce energy expenditure in the city by USD436.8 million. Emissions from the regional grid could be reduced by 12.2% in 2025, relative to business as usual trends, with investments of USD2.9 billion that would generate annual savings of USD175 million. These estimates understate the savings from reduced expenditure on energy subsidies and energy infrastructure. The compelling economic case for mainstreaming climate mitigation in this developing country city suggests that the constraints on climate action can be political and institutional rather than economic. There is therefore a need for more effective energy governance to drive the transition to a low-carbon economy. Highlights: We evaluate the economic case for low carbon investment in a developing world city. Cost-effective measures could reduce emissions by 24.1% relative to BAU levels. These pay for themselves in <1 year and generate savings throughout their lifetime. Further savings come from reduced expenditure on energy infrastructure, subsidies. Limitations on climate action seem to be political/institutional – not economic.